2016
DOI: 10.1534/genetics.116.191536
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Induces Cytokinesis Arrest in Cells Expressing a Mutated Sterol-14α-Demethylase in the Ergosterol Biosynthesis Pathway

Abstract: Hydroxyurea (HU) has been used for the treatment of multiple diseases, such as cancer. The therapeutic effect is generally believed to be due to the suppression of ribonucleotide reductase (RNR), which slows DNA polymerase movement at replication forks and induces an S phase cell cycle arrest in proliferating cells. Although aberrant mitosis and DNA damage generated at collapsed forks are the likely causes of cell death in the mutants with defects in replication stress response, the mechanism underlying the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 58 publications
(73 reference statements)
4
43
0
Order By: Relevance
“…Understanding the new cellkilling mechanisms of a well established small molecule drug with multiple clinical implications is of great importance for the development of novel therapeutics. We have recently shown that in the presence of sterol deficiency, HU causes cell lethality mainly by stably arresting S. pombe cells in cytokinesis (15). As we show in our next paper, 3 when applied with the inhibitors of heme or sterol biosynthesis, the cell-killing effect of HU can be significantly enhanced in S. pombe and S. cerevisiae, as well as in the opportunistic fungal pathogen Candida albicans.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Understanding the new cellkilling mechanisms of a well established small molecule drug with multiple clinical implications is of great importance for the development of novel therapeutics. We have recently shown that in the presence of sterol deficiency, HU causes cell lethality mainly by stably arresting S. pombe cells in cytokinesis (15). As we show in our next paper, 3 when applied with the inhibitors of heme or sterol biosynthesis, the cell-killing effect of HU can be significantly enhanced in S. pombe and S. cerevisiae, as well as in the opportunistic fungal pathogen Candida albicans.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, these mutants are not killed by aberrant mitosis or DNA damage that are commonly observed in DRC mutants but by previously unknown mechanisms. In a previous report, we showed that HU induces cytokinesis arrest in cells carrying a hypomorphic mutation in the erg11 gene, which encodes the enzyme sterol-14␣-demethylase required for sterol biosynthesis (15). In this study, we report the identification of a novel hem13-1 mutant in the heme biosynthesis pathway.…”
Section: Hydroxyurea (Hu)mentioning
confidence: 65%
See 3 more Smart Citations